Factors associated with HIV viremia in transgender women and transvestites in five Brazilian capitals, 2019-2021: a multicenter study - Claudia Renata dos Santos Barros; Elaine Monteiro Matsuda; Aline Borges Moreira da Rocha; Giselle Ibete Silva López-Lopes; Norberto Camilo Campos; Luís Fernando de Macedo Brígido; Katia Cristina Bassichetto; Maria Amelia de Sousa Mascena Veras (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To analyze factors associated with detectable HIV viremia among transgender women/transvestites (TWT) in five Brazilian capitals. Methods : This was a cross-sectional study using data from a sample of TWT with HIV-positive serology and detectable viral load (VL), between 2019 and 2021. The dependent and independent variables were, respectively: viral load measurement, socioeconomic/demographic characteristics; alcohol/drug use; and self-perceived mental health. Poisson regression with robust variance was used. Results : A total of 425 TWT tested positive for HIV and underwent VL measurement, 179 (42.0%) presented detectable viremia. Factors positively associated with detectability were: younger age (PR=2.26; 95%CI 1.13;4.51), poorer housing conditions (PR=2.72; 95%CI 1.30;5.68) and poor/very poor mental health (PR=1.70; 95%CI 1.08;2.66). The use of antiretroviral drugs was a protective factor against detectability (PR=0.29; 95%CI 0.30;0.61). Conclusion The factors associated with unsuppressed viral load highlight vulnerability related to gender identity that have a negative impact, despite the majority of participants being on antiretroviral therapy (ART).